High-temperature performance of non-polar (11–20) InGaN quantum dots grown by a quasi-two-temperature method - Wang, T; Puchtler, T; Zhu, T; Jarman, J; Oliver, R; Taylor, R (Wiley, 2017)
Non-polar (11–20) a-plane InGaN quantum dots (QDs) are one of the strongest candidates to achieve on-chip applications of polarised single photon sources, which require a minimum operation temperature of ∼200 K under thermoelectrically cooled conditions. In order to further improve the material quality and optical properties of a-plane InGaN QDs, a quasi-two-temperature (Q2T) method has been developed, producing much smoother underlying InGaN quantum well than the previous modified droplet epitaxy (MDE) method. In this work, we compare the emission features of QDs grown by these two methods at temperatures up to 200 K. Both fabrications methods are shown to be able to produce QDs emitting around the thermoelectric cooling barrier. The sample fabricated by the new Q2T method demonstrates more stable operation, with an order of magnitude higher intensity at 200 K comparing to the comparable QDs grown by MDE. A detailed discussion of the possible mechanisms that result in this advantage of slower thermal quenching is presented. The use of this alternative fabrication method hence promises more reliable operation at temperatures even higher than the thermoelectric cooling threshold, and facilitates the on-going development of high temperature polarised single photon sources based on a-plane InGaN QDs.